Narratives of lingua franca English for transnational mobility - Gallagher, Kay (Frontiers in Communication, 2024)
This paper explores, through narrative inquiry, the acquisition and use of English as a lingua franca in the careers of three transnationally mobile managers in the global hotel and hospitality industry. The narratives presented here are interwoven with the context in which the multinational participants were situated at the time of the study: the United Arab Emirates (UAE) which is diversifying economically and socially in preparation for the post-fossil fuel era. In a country where the temporary immigrant population vastly outumbers national citizens, participants' situated language practices are explored through narratives of their multilingual repertoires, while focusing on English as a key resource for their self-initiated transnational mobility. These personal stories of the acquisition and use of English as a global language weave a linguacultural web that connects the Gulf region across global space, people, and time. Participants tell of the utility of English for their careers, their mulitlingual repertoires, and their enjoyment of their temporary working lives in the Emirates. Such voices are seldom heard in the literature.